Spectroscopic Evaluation and Analytical Validation of Lead (Pb) Determination in River Water Using Atomic Absorption Spectrophotometry - Rati Nur Ainna; Erik Lotfi; Amrita Mitra (Journal of Chemical Learning Innovation, 2026)
Purpose of the study: This study aims to determine the presence or absence of lead (Pb) in the Kelay River water and to quantify its concentration using atomic absorption spectrophotometry as a reliable analytical technique for environmental monitoring. Methodology: This study used atomic absorption spectrophotometry (Varian Spectr AA) for analysis. Supporting tools included analytical balance (KERN ALJ 220-4 NM), volumetric glassware (Pyrex), and electric heater. Methods involved judgment sampling, acid digestion using HNO3, preparation of Pb(NO3)2 standard solutions, calibration curve construction, and linear regression analysis. Main Findings: Lead (Pb) was detected in Kelay River water samples. The concentrations in samples D and E were 0.0773 mg/L and 0.0634 mg/L, respectively, exceeding acceptable limits. In contrast, samples A, B, and C showed concentrations below 0.01 mg/L. The calibration curve exhibited strong linearity with a high correlation coefficient. Novelty/Originality of this study: This study applies an analytical spectroscopy-based approach to determine lead (Pb) levels in a specific river system with consideration of local environmental characteristics. It integrates calibration and detection limit evaluation, contributing to improved analytical reliability and providing new data for environmental assessment in underreported regions.